THE CORRELATION BETWEEN LOW BIRTHWEIGHT (LBW) WITH INFANT MORTALITY RATES (IMR) AND ANTENATAL CARE (ANC) IN EAST JAVA 2018 - Salsabila Naim; Yuly Sulistyorini; Yudi Evriyanto; Evi Yuniati (Universitas Airlangga, 2020)
Nearly 15 % of babies worldwide are born with LBW. The proportion of LBW in East Java was 6.61% higher compared to nationwide 6.2% in 2018. The East Java ranked third for the highest IMR in Indonesia, LBW as the most significant cause (42%). One of determinants for birthweight is ANC. The proportion of the first ANC was 88.25%, and the complete ANC was 80.2% in East Java in 2018. The proportion of the province's complete ANC was lower than the national by 95.2%. This research is a secondary quantitative data analytic, sourced from the Health Profiles of East Java Province in 2018. This study aims to describe the strong correlation between LBW and IMR and ANC in the province of East Java using Pearson correlation analytic. The results showed that there was a correlation with influential and unidirectional forces between LBW and IMR. There was a correlation of moderate strength between the complete ANC visit and LBW. There wasn’t significant correlation between the first ANC and LBW. The government in East Java must make solution to increase complete ANC visit by searching the causes factors of low proportion of it.